Experimental Investigations on Electrical Charge of Precracked Rock Specimens under Uniaxial Compression. (31st October 2020) - He, Feng; Wang, Zhenwei; Zhao, Yangfeng; Song, Gaofeng; Liu, Bowen
Abstract : The electrical charge characteristic of rock materials under compression is an important index for predicting the development of rock fractures and the failure of engineering structures. However, the charge behaviours of a preexisting rock sample have not been studied in depth. In this study, sandstone samples with a single fabricated precrack at different angles of inclination are prepared. The uniaxial compression tests are performed to study the charge behaviours associated with the initiation and propagation of secondary cracks, the mechanical properties, and the progressive failure of stressed rock samples. An improved analytical model based on the maximum tensile stress failure theory for brittle materials is also proposed for determining the crack growth paths of the single precrack rock samples under uniaxial compression. The friction factors of crack surfaces are computed. The results show that the step functions on the curves of charge accumulation over time correspond to the fluctuation of stress, indicating the initiation of microcracks. The sample with a crack inclination angle of π / 4 shows the largest amount of both the first charge and the total accumulation. The analytical model shows a positive relationship between the crack face friction factors and the charge accumulation. The analytical solution of the crack development angles shows good agreement with the experimental results. This work may provide reference for the similar studies regarding the correlation of charging behaviours to the compressed rock materials.